RAPD analysis of Sclerotium rolfsii isolates causing collar rot of eggplant and tomato (International Journal of Agricultural Research, Innovation and Technology, 2016)
Eight isolates of Sclerotium rolfsii from four strategically geographical sites of Bangladesh were characterized and their cultural properties like average linear mycelial growth, colony colour, colony consistency, growth pattern and sclerotia formation were studied. Isolates varied in mycelial growth and other growth characteristics and were grouped into three. The highest linear growth was displayed by S8. DNA concentration of eight isolates varied from 1150-7200 ng/?l. DNA fingerprinting by RAPD prompted the grouping of isolates. Selected 3 primers generated 20 bands with size ranging from 100-1500 bp. Out of the 20 bands, 9 bands (45%) were polymorphic and 11 bands (55%) were monomorphic among the eight isolates of Sclerotium rolfsii. The co-efficient of gene differentiation (Gst) was 1.000 reflecting the existence of high level of genetic variations among the 8 isolates. The lowest genetic distance and highest inter isolate similarity was found in S1 and S2 which would be homogeneous. The highest genetic distance and lowest inter isolate similarity found in S3, S7 and S3, S8 pair which would be most divergent isolates. The cluster analysis also revealed that S3, S7 and S8 belong to different clusters. All five varieties of eggplant and tomatoes were graded as susceptible when inoculated with eight isolates. Plant mortality 93.33% was recorded in S4, S6 and in S8. Considering the isolate factor the most virulent isolate would be S8 whereas the less virulent isolate would be S2 and S7. Host plant of S8 was tomato collected from Thakurgaon. S2 and S7 were collected from BAU farm and Dinajpur and host plants were lentil and tomato respectively. It is evident that Sclerotium rolfsii from Thakurgaon on host tomato is more virulent.Int. J. Agril. Res. Innov. & Tech. 6 (1): 47-57, June, 2016